2011
DOI: 10.1086/657022
|View full text |Cite
|
Sign up to set email alerts
|

On the Heritability of Consumer Decision Making: An Exploratory Approach for Studying Genetic Effects on Judgment and Choice

Abstract: While constructed preferences have received a great deal of attention, there has been virtually no research regarding the genetic basis of consumer judgment and choice. In this research, we examine a wide range of previously unexplored heritable effects on consumer choices and judgments. Moreover, whereas prior research on heritable traits has typically employed a piecemeal approach, demonstrating each heritable trait separately, we propose an alternative way to simultaneously explore common mechanisms and lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
42
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(49 citation statements)
references
References 81 publications
6
42
0
1
Order By: Relevance
“…They found significant heritability for 7 out of 23 product preferences surveyed (e.g., for dark chocolate, hybrid cars, and science fiction), and for 13 out of 39 items concerning consumer judgment and decision making (e.g., compromise options, loss aversion, near-future temporal discounting, and maximizing versus satisfying). Near the conclusion of their article, Simonson and Sela (2011) suggested that twin research might reveal the genetic predispositions that lead certain consumers to prefer a certain type of mobile phone, which leads nicely to our study.…”
supporting
confidence: 62%
“…They found significant heritability for 7 out of 23 product preferences surveyed (e.g., for dark chocolate, hybrid cars, and science fiction), and for 13 out of 39 items concerning consumer judgment and decision making (e.g., compromise options, loss aversion, near-future temporal discounting, and maximizing versus satisfying). Near the conclusion of their article, Simonson and Sela (2011) suggested that twin research might reveal the genetic predispositions that lead certain consumers to prefer a certain type of mobile phone, which leads nicely to our study.…”
supporting
confidence: 62%
“…We build on an emerging literature wherein behavioral genetic techniques are used to study the genetic and environmental sources of variation in economic decision making (Barnea et al 2010;Cesarini et al 2008Cesarini et al , 2009aCronqvist and Siegel 2011;Simonson and Sela 2011;Zhong et al 2009;Zyphur et al 2009;Wallace et al 2007). We find that well-documented behavioral anomalies such as the conjunction fallacy, loss aversion, default bias, and representativeness are moderately heritable.…”
Section: Discussionmentioning
confidence: 99%
“…More recent work has extended the literature by studying the genetic heritability of the formation of preferences (Cesarini et. al 2009, andSimonson andSela 2011) and financial decision-making (Barnea et al 2010, andCesarini et al 2010 Most of the attrition is due to death (e.g., of fatal diseases or accidents) and migration. 10 There are two other closely related branches in the literature.…”
Section: Existing Evidencementioning
confidence: 99%